2021
DOI: 10.1177/03400352211024675
|View full text |Cite
|
Sign up to set email alerts
|

How older adults in the USA and India seek information during the COVID-19 pandemic: A comparative study of information behavior

Abstract: The 2020 COVID-19 pandemic introduced significant information challenges for older adults worldwide. Given the widespread disparities in information infrastructure and access between developing and developed countries, the challenges presented during this period may be even more grave in the developing world. This interview study examines how older adults (age 65+) in two countries—the USA and India—experienced information needs, sources, and barriers. The results indicate distinct experiences among the two po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The impact of the information uncertainty and infodemic on the public is significantly reduced. Different from the current study, research during the subsequent stages has paid more attention to the universal information needs and influencing factors, and then improve the information service (Zhao and Basnyat, 2022;Li et al, 2022;Lund and Maurya, 2022).…”
Section: Formation Of the Public's Information Needsmentioning
confidence: 93%
“…The impact of the information uncertainty and infodemic on the public is significantly reduced. Different from the current study, research during the subsequent stages has paid more attention to the universal information needs and influencing factors, and then improve the information service (Zhao and Basnyat, 2022;Li et al, 2022;Lund and Maurya, 2022).…”
Section: Formation Of the Public's Information Needsmentioning
confidence: 93%
“…Specifically, COVID-19 has shown that family work around health information search has extended to nonimmigrant population, in which children act as online searchers for their families (Drouin et al , 2020). As the geriatric population grows, senior citizens are also asking their adult children to act as online health search and brokers (Lund and Maurya, 2021). Therefore, we believe our model for OSB has utility for many kinds of online searching as family work.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Several studies have applied the sense-making theory to investigate an individual's information-seeking behavior during the COVID-19 pandemic. Most people, particularly the vulnerable (for example, older persons in remote regions), experience unmet "needs" and "barriers" to accessing information during the COVID-19 pandemic [13]. In addition, young individuals are concerned for their vulnerable elderly parents or relatives [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, young individuals are concerned for their vulnerable elderly parents or relatives [14]. According to a study comparing information-seeking among older adults in the U.S. and India, the national context may be important in information-seeking during the COVID-19 pandemic [13]. This study discovered differences in information needs and utilization of information sources between these two groups, implying that the national context may be important in information-seeking during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%